Karakteristik Penderita Diabetes Melitus dengan Tuberkulosis di RSUD Abdoel Wahab Sjahranie Tahun 2022-2023: Characteristics of Diabetes Mellitus Patients with Tuberculosis at Abdoel Wahab Sjahranie Regional General Hospital during 2022-2023 - Falah, Irdiansyah Al; Sawitri, Endang; Retnaningrum, Yuliana Rahmah (Jurnal Sains dan Kesehatan, 2025)
Individuals with diabetes mellitus have a weakened immune system, making them 2-3 times more vulnerable to tuberculosis than those without the condition. This study is to investigate the characteristics of diabetic mellitus patients with tuberculosis at Abdoel Wahab Sjahranie Regional Public Hospital (RSUD) from 2022 to 2023. This observational study employed a cross-sectional design and examined 67 medical records of individuals diagnosed with both diabetes mellitus and tuberculosis between 2022 and 2023. This research examined 67 medical records of diabetes mellitus patients diagnosed with tuberculosis at Abdoel Wahab Sjahranie Regional Public Hospital (RSUD) throughout the period of 2022-2023. The results show that the age group of patients This study analyzed 67 medical records of diabetes mellitus patients with tuberculosis at Abdoel Wahab Sjahranie Regional Public Hospital (RSUD) in 2022-2023. The findings showed that 12 patients were aged 19-44 years, 38 patients were aged 45-59 years, and 17 patients were aged ?60 years. In terms of gender distribution, 48 patients were male, while 19 patients were female. Based on Body Mass Index (BMI), 4 patients were classified as severely underweight, 17 patients as mildly underweight, 25 patients had a normal BMI, 10 patients were mildly overweight, and 11 patients were severely overweight. Regarding HbA1c levels (glycemic control), 0 patients had good glucose control, while 29 patients had moderate control, and 38 patients had poor glucose control. The most commonly used treatment was combination therapy with RHZE (Rifampin, Isoniazid, Pyrazinamide, and Ethambutol) and insulin, administered to 19 patients. Bacteriological examination results indicated that 55 patients had detected tuberculosis bacteria, while 12 patients had undetected bacteria. In terms of prognosis, 31 patients not survived, while 36 patients survived. The study concludes that most diabetes mellitus patients with tuberculosis at Abdoel Wahab Sjahranie Regional Public Hospital (RSUD) during 2022-2023 were male, aged between 45 and 59 years, exhibiting a normal BMI, poor glycemic control as indicated by HbA1c levels, receiving combination treatment of RHZE with insulin, showing positive bacteriological test results, and having a survival prognosis. Keywords:          Diabetes Mellitus, Tuberculosis, Risk Factors, Management, Prognosis   Abstrak Penderita diabetes melitus memiliki sistem kekebalan tubuh yang lemah sehingga berisiko 2-3 kali lebih tinggi untuk terkena tuberkulosis dibandingkan dengan orang yang tidak memiliki diabetes melitus. Penelitian ini bertujuan untuk mengetahui karakteristik penderita diabetes melitus dengan tuberkulosis di RSUD Abdoel Wahab Sjahranie tahun 2022-2023. Penelitian observasional deskriptif dengan pendekatan cross sectional ini menggunakan 67 data rekam medis pasien diabetes melitus dengan tuberkulosis tahun 2022-2023. Hasil penelitian menunjukkan rentang usia 19-44 tahun = 12 penderita, 45-59 tahun = 38 penderita, >60 tahun = 17 penderita. Jenis kelamin laki-laki = 48 penderita dan perempuan = 19 penderita. Indeks massa tubuh kurus tingkat berat = 4 penderita, kurus tingkat ringan = 17 penderita, normal = 25 penderita, gemuk ringan = 10 penderita, dan gemuk berat = 11 penderita; nilai HbA1c didapatkan kontrol glukosa baik = 0 penderita, kontrol glukosa sedang = 29 penderita, kontrol glukosa buruk = 38 penderita; pengobatan yang paling banyak digunakan adalah terapi kombinasi RHZE (Rifampisin, Isoniazid, Pirazinamid, dan Etambutol) dengan insulin dengan jumlah 19 penderita, bakteriologis detected = 55 penderita, dan not detected = 12 penderita, prognosis meninggal = 31 penderita, dan hidup = 36 penderita. Disimpulkan bahwa penderita diabetes melitus dengan tuberkulosis di RSUD Abdoel Wahab Sjahranie tahun 2022-2023 terbanyak adalah laki-laki usia 45 hingga 59 tahun, IMT normal, HbA1c kategori kontrol glukosa buruk, pengobatan kombinasi RHZE (Rifampisin, Isoniazid, Pirazinamid, dan Etambutol) dengan insulin, pemeriksaan bakteriologis terdeteksi, dan prognosis hidup. Kata Kunci:         Diabetes Melitus, Tuberkulosis, Faktor Risiko, Tatalaksana, Prognosis